2023
DOI: 10.1177/1759720x221149965
|View full text |Cite
|
Sign up to set email alerts
|

Association between baseline cardiovascular risk and incidence rates of major adverse cardiovascular events and malignancies in patients with psoriatic arthritis and psoriasis receiving tofacitinib

Abstract: Background: Tofacitinib is a Janus kinase inhibitor for the treatment of psoriatic arthritis (PsA) and has been investigated for psoriasis (PsO). Objectives: This post hoc analysis examined baseline cardiovascular (CV) disease risk and its association with the occurrence of major adverse cardiovascular events (MACE) and malignancies in tofacitinib-treated patients with PsA and PsO. Design: Included three phase III/long-term extension (LTE) PsA trials and seven phase II/phase III/LTE PsO trials of patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 46 publications
(114 reference statements)
2
13
0
1
Order By: Relevance
“…Additionally, the STAR-RA study reported that RA patients on tofacitinib had no increased cardiovascular risk whilst those with a cardiovascular disease history did4 . A post-hoc analysis of PsA patients on tofacitinib had similar findings5 . Data on other JAKi also demonstrated no increased risk.…”
supporting
confidence: 60%
See 2 more Smart Citations
“…Additionally, the STAR-RA study reported that RA patients on tofacitinib had no increased cardiovascular risk whilst those with a cardiovascular disease history did4 . A post-hoc analysis of PsA patients on tofacitinib had similar findings5 . Data on other JAKi also demonstrated no increased risk.…”
supporting
confidence: 60%
“…Huang W 1,11 , Luo S 2,11 , Chen D 3,11 , Tsai C 4,11 , Hsieh S 5,11 ,Lu L 6,11 , Jan Wu Y 7,11 , Chen M 4,11 , Hsieh T 1,11 , Yeh F 8,11 , Su Y 9,11 , Liao Y 1,11 , Lee T 10,11 , Sheu H Therefore, the in vitro experimental method of using inflammatory cytokines such as interleukin-1 beta (IL-1ß) to create an inflammatory environment in two-dimensional (2D) monolayer culture is certainly different from the in vivo inflammatory environment of OA. In addition, the effects of various factors affecting the survival/engraftment of administered cells can be evaluated in a 3D co-culture system composed of spheroids created from different lineage cells within the joint cavity that would better mimic the inflammatory environment of OA.…”
Section: Taiwan Consensus Recommendations On the Management Of System...mentioning
confidence: 99%
See 1 more Smart Citation
“…The findings that women and young adults may warrant closer monitoring for tofacitinib-associated dyslipidemia could inform more tailored RA treatment approaches. No differences in lipid response to tofacitinib versus adalimumab were observed by race, contrasting with some cardiovascular studies showing higher event risks in minorities (Khosrow-Khavar et al, 2022;Kristensen et al, 2023a;Kristensen et al, 2023b;Schreiber et al, 2023). This study was limited by potential misclassification bias, lack of treatment dose-response data, and inability to make conclusions about long-term MACE risks.…”
Section: Discussionmentioning
confidence: 72%
“…Considering this scenario, a recent post-hoc analysis of various phases of clinical trial study reported that tofacitinib exposure, a Janus kinase inhibitor used for PsA treatment, increase the incidence rate (IR, with 95% CI) of major adverse cardiovascular event/MACE in whom had a baseline history of atherosclerotic CVD (ASCVD) [0.75 (0.02-4.21)], followed by the high (≥ 20%) 10-year risk of ASCVD [1.37 (0.03-7.63)], and the high risk of malignancies [1.13 (0.45-2.33)] in a subset of PsA patients [56]. The highest IR of MACE with a history of ASCVD [1.87 (0.69-4.08)], a high 10-year risk of ASCVD [1.49 (0.55-3.24)], followed by the high risk of malignancy [3.48 (1.90-5.83)] was reported in the PsD patients 54 .…”
Section: Psoriatic Cardiovascular Disease/cvdmentioning
confidence: 99%